Gambaran Perilaku Pola Makan Penderita Stroke pada Lansia Di Wilayah Puskesmas Pematang Panjang Kecamatan Air Putih Kabupaten Batu Bara Tahun 2021 - Johana Pulcher Naibaho (Syntax Corporation Indonesia, 2022)
Background: The incidence of stroke can be caused by several factors, namely gender, age, education, occupation, religion, and ethnicity. And as for the factors that cause stroke from diet are unhealthy food consumption, lack of exercise, alcoholic drink addicts, and unhealthy lifestyles. Research Objectives: To find out the description of the eating pattern of stroke sufferers in the elderly in Pematang Panjang Public Health Center, Air Putih District, Batu Regency. Bara in 2021. Research Methods: This study uses a descriptive method where data collection is carried out using FFQ (frequency food questionnaire) as many as 70 respondents. The research instrument used a food frequency questionnaire (FFQ). Research Results: The results obtained from 70 respondents in Pematang Panjang Village that eating behavior was very good by 21.4%, elderly who had good eating behavior were 28.5%, elderly who had moderate/moderate eating behavior were 14.2 %, then the elderly who have bad eating behavior are 21.4%, and the elderly who have very bad eating behavior are 14.2%. Conclusion: Based on the respondent's diet, foods that are not recommended for stroke sufferers are still often consumed, namely coconut oil, a food that is high in fat and has an effect on increasing cholesterol in the blood. Suggestion: Stroke respondents are advised to adjust their diet, avoid eating foods that are high in fat and cholesterol (offal, coconut milk, meat, the use of coconut/palm oil), reduce the use of salt or replace it with dietary salt. doing regular physical activity, reducing stress levels by doing lots of activities outside the home, taking vacations, doing sports such as gymnastics, yoga, can reduce stress levels, and stop smoking to prevent strokes.